APLIKASI MEDIA PEMBELAJARAN ENGLISH LEARNING BERBASIS ANDROID - Alwi Perdana Aritonang; Raissa Amanda Putri (Smart Education, 2024)
Abstract: The English learning system has a very important role for junior high school students. However, in the application of learning English there are ups and downs of requests for students at schools where the learning system is still inefficient in teaching english material. In This Case, The Great Ta English Course develops an English learning media application for the course. This study aims to design an Android-based English learning media application. Which is one way to make it easier for students and even a teacher to provide an English language teaching system that is more detailed, more fun, effective and efficient. The research method used is R&D (Researce and Development) with data collection methods through interviews, observation, and literature study. The system development method used is the Waterfall SDLC model. System development stages include analysis, design, coding, and testing. The Laravel framework is used to display the English language learning application interface. PHP as well as MySQL database is used for coding. Testing using a black box. Keywords: PHP, MYSQL, R&D, SDLC Abstrak: Sistem pembelajaran Bahasa Inggris memiliki peran yang sangat penting bagi siswa siswi Sekolah Menengah Pertama. Namun, dalam pengaplikasian pembelajaran Bahasa Inggris mengalami naik turun pemintan terhadap siswa siswi pada sekolah yang sistem pembelajarannya masih kurang efesien dalam mengajarkan materi Bahasa Inggris. Dalam hal ini, Great Ta English Course mengembangkan sebuah aplikasi media pembelajaran english learning pada kursus tersebut. Penelitian ini bertujuan untuk merancang sebuah aplikasi media pembelajaran english learning berbasis android. Yang dimana menjadi salah satu cara untuk memudahkan siswa siswi bahkan seorang pengajar dapat memberi sistem pengajaran Bahasa Inggris yang lebih detail, lebih menyenangkan, efektif dan efisien. Metode penelitian yang digunakan adalah R&D (Researce and Development) dengan metode pengumpulan data melalui wawancara, observasi dan studi pustaka. Metode pengembangan sistem yang digunakan adalah SDLC model Waterfall. Tahapan pengembangan sistem meliputi analisis, desain, pengkodingan dan pengujian. Framework Laravel digunakan untuk tampilan interface aplikasi pembelajaran Bahasa Inggris. PHP serta database MySQL digunakan untuk pengkodingan. Pengujian menggunakan black box. Kata kunci: PHP, MYSQL, R&D, SDLC